Radiofrequency based hyperthermia therapy: a centennial technique serving modern surgery - Berjano, E. J.; Romero Méndez, R.; Franco, W. (Revista Mexicana de Ingenieria Biomedica, 2010)
Although the use of radiofrequency (RF) electric currents to treat very different illnesses by surgical means (e.g. cancer, disturbances in cardiac rhythms, or hyperopia) is very recent, the biophysical phenomena in which these surgical techniques are based has been understood for more than 100 years. The aim of this paper is to didactically present the use of RF currents to heat biological tissues with therapeutic and surgical purposes. First, the underlying biophysics mechanisms of this approach are explained. Next, different examples of recent clinical RF-current based applications are discussed.